Experimental study on the steel–concrete bond behaviour of circular concrete-filled stainless steel tubes. (December 2021) - Dai, Peng; Yang, Lu; Wang, Jie; Fan, Junwei; Lin, Manfang
Abstract: The paper reports an experimental investigation on the bond stress–slip relationship in concrete-filled stainless steel tube (CFSST) structures. Push-out tests were conducted on twelve specimens covering two stainless steel grades, two concrete grades, two cross-sectional dimensions and two internal ring conditions (with and without the internal ring). The effects of these factors on the bond stress–slip relationship in CFSST members were analysed and discussed. A theoretical model, based on the assumption that no restraining force from the steel tube was applied to the concrete core, was developed to predict the bond stress–slip response of CFSSTs and was evaluated against the test results. An empirical model was also proposed based on regression analysis to replicate the experimental bond stress–slip relationships, which can be used as input data for analytical and numerical simulations in future studies of CFSST structures. Highlights: Push-out tests on twelve CFSST specimens were carried out. The effects of different factors on τ - S relationship were analysed and discussed. A bond stress–slip model assuming no confinement was developed. Based on the experimental τ - S relationships, an empirical model was proposed.